2013
DOI: 10.1007/s12035-013-8551-2
|View full text |Cite
|
Sign up to set email alerts
|

Nod-Like Receptor Protein 1 Inflammasome Mediates Neuron Injury under High Glucose

Abstract: Diabetic encephalopathy is one of the most common complications of diabetes. Inflammatory events during diabetes may be an important mechanism of diabetic encephalopathy. Inflammasome is a multiprotein complex consisting of Nod-like receptor proteins (NLRPs), apoptosis-associated speck-like protein (ASC), and caspase 1 or 5, which functions to switch on the inflammatory process and the release of inflammatory factors. The present study hypothesized that the formation and activation of NLRP1 inflammasome turns … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 58 publications
3
34
0
4
Order By: Relevance
“…Although inflammasomes are generally formed in inflammatory immune cells, accumulating evidences have indicated that distinct types of inflammasomes are also present in neurons. NLRP1 inflammasomes mediate neuron injury under high glucose [43]. High extracellular potassium opens pannexin channels leading to inflammasome activation in primary neurons and astrocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although inflammasomes are generally formed in inflammatory immune cells, accumulating evidences have indicated that distinct types of inflammasomes are also present in neurons. NLRP1 inflammasomes mediate neuron injury under high glucose [43]. High extracellular potassium opens pannexin channels leading to inflammasome activation in primary neurons and astrocytes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory processes are thought to play a role in neuronal degeneration (Meng et al, 2013; Morales et al, 2010). In addition to astrocytes and microglia, neurons also contribute to the inflammatory response in the CNS by releasing cytokines, e.g.…”
Section: Inflammatory Process In Admentioning
confidence: 99%
“…A β and prion proteins are potent activators of the (NLR family, pyrin domain-containing) NLRP3 inflammasome [3840]. NLRP1 and NLRP5 are known to contribute to neuronal death [41]. A β induced IL-1 β release in microglia through NLRP3 [42].…”
Section: Molecular Mediatorsmentioning
confidence: 99%